(untitled) (Ekonomski vjesnik/Econviews - Review of Contemporary Business, Entrepreneurship and Economic Issues, 2021)
Purpose: New products are vital to the success of firms and represent opportunities for business growth and development. The transition from the idea to the launch of a new product represents a process as complex as it is interesting for a firm. This is especially true for banking products. The purpose of this paper is to analyze how much a bank strategy influences the development of new banking products and whether customer preferences have an impact on the launch of new products by commercial banks. Methodology: Regression model, correlation, KMO and Bartlett‘s test will be used to analyze the impact of independent variables on the launch of new products on the market. Results: The results of this research show that the strategy of Kosovo commercial banks influences the creation and development of new products. Conclusion: Therefore, it can be said that commercial banks do not lack strategies which have the launch and creation of new products as their element. Banks also take into account customer and society requirements regarding the development of new products.